(untitled) (Arquivo Maaravi: Revista Digital de Estudos Judaicos da UFMG, 2021)
In Noemi Jaffe’s novel Írisz: as orquídeas, published in 2015, a Hungarian immigrant moves to Brazil, abandoning, in this movement, her homeland, mother and partner. In São Paulo, at Jardim Botânico neighborhood, the narrator voice is dedicated to the study of orchids, flowers that will be a metaphor for this floating and exiled character, whose aerial and parasitic roots characterize her erratic character. Furthermore, together with the mutability of the protagonist, who avoids taking roots, her study of orchids translates into an analysis of the language, a trait that seems to mark Írisz’s narrative. Thus, this communication will analyze, from orchids, the fictionalization of a family history and the elaboration of fragmented, dispersed and undecipherable memories.